The spatio-temporal change in soil P and P-solubilizing bacteria under clover mulching in apple orchards of Loess Plateau. (October 2022) - Wang, Yuanji; Liu, Li; Hu, Yu; Zhang, Jiatao; Jia, Rongjian; Huang, Qianqian; Gao, Hua; Awasthi, Mukesh Kumar; Li, Huike; Zhao, Zhengyang
Abstract: Cover crop is an effective practice for improving soil quality and increase soil nutrients. However, the spatio-temporal change of soil phosphorus (P) components and P-solubilizing microorganisms in the process of grass succession is not evident. Here, we studied the variation of soil P components and P-solubilizing bacteria at 0–60 cm soil layer under clean tillage (CT) and white clover (WC, Trifolium repens L.) grown for 5, 9, and 14 years in an apple test station on the Loess Plateau, China. This study suggested that clover cover could effectively increase the total P, available P (AP), microbial P, organic P (Po), and inorganic P (Al–P, Ca2 –P, Ca8 –P and Fe–P) in topsoil (0–20 cm) and AP, Po and inorganic P at 20–40 cm soil layer to improve the soil P bioavailability. The effects of WC living mulch on the soil P forms were more significant with the increase in grass growing years, but this effect was difficult to extend to deep soil. In addition, the WC treatments were beneficial to the growth of P-solubilizing microorganisms in surface soil and improved the alkaline phosphatase activity at 0–40 cm soil layer, mainly including Bacillus, Bradyrhizobium, Nocardioides, Sphingomonas and Streptomyces . This study provided a perspective on the dynamic changes of soil P forms and P-solubilizing microorganisms and under long-term cover crop. Graphical abstract: Image 1 Highlights: Clover cover could increase Al–P, Ca2 –P, Ca8 –P and Fe–P in topsoil. Effect of clover cover on soil P increased with grass growing years. Clover cover increased Bacillus, Bradyrhizobium, Nocardioides, Sphingomonas and Streptomyces . Clover cover had no significant influence on P in deep soil.